Transitioning HIV-infected adolescents to adult care at 14 clinics across the United States: using adolescent and adult providers' insights to create multi-level solutions to address transition barriers. Issue 10 (3rd October 2017) - Philbin, Morgan M.; Tanner, Amanda E.; Chambers, Brittany D.; Ma, Alice; Ware, Samuella; Lee, Sonia; Fortenberry, J. Dennis; the Adolescent Trials Network,
ABSTRACT: HIV-infected adolescents have disproportionately low rates of care retention and viral suppression. Approximately half disengage from care while transitioning to adult clinics, in part due to fragmented care systems and lack of streamlined protocols. We conducted 58 qualitative interviews with social service and health care providers across 14 Adolescent Trials Network clinics ( n  = 28) and 20 adult clinics that receive transitioning adolescents ( n  = 30) from August 2015–June 2016. We used the constant comparative approach to examine processes, barriers, and facilitators of adult care transition. Transition barriers coalesced around three levels. Structural : insurance eligibility, transportation, and HIV-related stigma; Clinical : inter-clinic communication, differences in care cultures, and resource/personnel limitations; and Individual : adolescents' transition readiness and developmental capacity. Staff-initiated solutions (e.g., grant-funded transportation) were often unsustainable and applied individual-level solutions to structural-level barriers. Comprehensive initiatives, which develop collaborative policies and protocols that support providers' ability to match the solution and barrier level (i.e., structural-to-structural), are sorely needed. These initiatives should also support local systematic planning to facilitate inter-clinic structures and communication. Such approaches will help HIV-infected adolescents transition to adult care and improve long-term health outcomes.